PERAN KEMAMPUAN SOSIAL DALAM MENDORONG PARTISIPASI SISWA PADA PEMBELAJARAN IPS SD - Maulidya, Aisyah; Varathi, Khansa Ihtisyam; Marini, Arita; Yunus, Mahmud (Cahaya Ilmu Bangsa Institute, 2024)
Social skills are the ability of individuals to interact and communicate effectively, encompassing elements such as empathy, cooperation, and good communication. In an educational context, social skills are essential for students’ academic success and emotional well-being, as well as helping them build positive relationships with peers and teachers. Social Studies (IPS) learning in Elementary Schools aims to develop students’ understanding of society and human interaction, as well as to shape the character and social skills needed to become good citizens. Learning methods such as project-based and group discussions can increase student participation, but barriers such as lack of interest and monotonous teaching methods can interfere with engagement. Research shows that social skills have a significant impact on student participation in learning, and the application of cooperative methods can improve social skills as well as academic learning outcomes. Thus, the integration of social skills in IPS learning can create a more interactive learning environment and support the development of student character.